A comparative study on the efficacy of fractional CO2 laser and fractional CO2 laser with autologous platelet-rich plasma in scars - Satish Godara; Sandeep Arora; Rajeshwari Dabas; Gulhima Arora; Gopi Renganathan; Richa Choudhary (Wolters Kluwer Medknow Publications, 2020)
Context: Surgical correction of scars may not be an ideal solution in all cases and hence it is desirable to have a nonsurgical option available. Autologous platelet-rich plasma (PRP) and fractional carbon dioxide laser (FCL) offer an alternative treatment modality. Aims: To compare the efficacy and safety of FCL and intradermal PRP with FCL in the management of postburn and posttraumatic scars. Settings and Design: A prospective, randomized, observer-blinded, comparative study was conducted at a hospital skin centre from Oct 2016 to Sep 2018. Subjects and Methods: A total of 67 patients with scars were randomly divided into two groups; Group I was treated with four sessions of monthly FCL and Group II was treated with four sessions of PRP and FCL. The patients were assessed using the Patient and Observer Scar Assessment Scale (POSAS) at baseline and 4 weeks after each session. Statistical Analysis Used: For continuous variables, the summary statistics of mean ± standard deviation was used; for categorical data, number and percentage were used. Chi-square (χ2) test was used for association between two categorical variables. P value <0.05 was considered to be statistically significant. Results: Thirty cases in each group completed the study. There was a significant improvement in the total score of POSAS (p < 0.001) in both groups, but the final difference between the two groups was not statistically significant (p = 0.793 and P = 0.278, respectively). Conclusions: Fractional CO2 laser causes significant improvement in scar appearance. PRP in combination with FCL offers no additional advantage.